Prisoners Of Hope. - Calvert, Michael, 1913- (Pen & Sword paperback., 2004)
Of the many thousands of books that have been written about the Second World War, Prisoners of Hope is one of the very few acknowledged masterpieces. A devoted disciple of Wingate, of Chindit fame, Calvert accompanied him on the first controversial journey behind the Japanese lines, and after Wingate's tragic death, became the lading protagonist on behalf of Wingate's ideas and the staunchest defender of his reputation. Prisoners of Hope is the classic work on Guerilla warfare as experienced by the commander in action.